SEMI-THEORETICAL APPROACH TO THE EFFECT OF ROUGHNESS ON THE RELATIVE HEIGHT OF THE HYDRAULIC RESSAGE EVOLVING IN A TRIANGULAR CHANNEL - S. Kateb; A. Ghomri; M. Debabeche (Journal of Fundamental and Applied Sciences, 2018)
The study aims to analyze the theoretical and experimental jump evolving in a triangular channel with a rough bottom. The principal goal of the study is to find a general relationship connecting the relative downstream height and the channel bottom roughness. This study will show also that the channel roughness contributes in the decrease of the downstream height of the jump.